1978
DOI: 10.1071/ar9780181
|View full text |Cite
|
Sign up to set email alerts
|

The induction of reproductive activity in lactating ewes

Abstract: In two experiments, Merino ewes that had lambed in either the autumn or spring were treated with various combinations of a progestagen (methylacetoxyprogesterone, MAP) and pregnant mare's serum gonadotrophin (PMSG), from 3 days post partum. Irrespective of the season of lambing, the treatments resulted in ovulation in nearly all ewes before day 15 post partum; oestrus was observed in all ewes that had lambed in the autumn but in only half the spring ewes. Regular oestrus activity was not resumed after the indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 9 publications
1
5
0
1
Order By: Relevance
“…While lactation is reported to lower fertility when ewes were bred within 30 days postpartum (Restall et al 1978) and increase the postpartum anoestrus interval (Mallampati et al 1954), Hulet & Foote (1967) found no effect of lactation on the number of ewes lambing when breeding occurred 30-90 days postpartum. In Australia, Dawe et al (1969) achieved 65% pregnancy rates in Border Leicester × Merino ewes that had been lactating for 9 weeks prior to the mating period, during the non-breeding season.…”
Section: Introductionmentioning
confidence: 98%
“…While lactation is reported to lower fertility when ewes were bred within 30 days postpartum (Restall et al 1978) and increase the postpartum anoestrus interval (Mallampati et al 1954), Hulet & Foote (1967) found no effect of lactation on the number of ewes lambing when breeding occurred 30-90 days postpartum. In Australia, Dawe et al (1969) achieved 65% pregnancy rates in Border Leicester × Merino ewes that had been lactating for 9 weeks prior to the mating period, during the non-breeding season.…”
Section: Introductionmentioning
confidence: 98%
“…These systems all recommend early weaning of lambs in order to improve fertility in spring matings, but early weaning is often not consistent with forage-based lamb production. Attempts to breed lactating ewes in spring have consistently been disappointing (Bourke, 1964;Whiteman et al, 1972;Cognie et al, 1975;Pope et al, 1989), and use of hormone or light manipulation to improve spring fertility has generally not been successful in lactating ewes (Restall et al, 1978;de Nicolo et al, 2006;Martemucci and D'Alessandro, 2010). Selection to improve ewe fertility in a crossbred (50% Dorset, 25% Rambouillet, 25% Finnish Landrace) sheep population mated in May and June at Virginia Tech (37°N latitude) resulted in significant selection response (Notter and Cockett, 2005) and correlated increase in duration of the breeding season (Vincent et al, 2000;Notter et al, 2011;Goff et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite successful fertilization at an induced oestrus 28 days after parturition, no pregnancies were sustained and there was a high incidence of inadequate luteal function in lactating ewes induced to ovulate by using progestagen pessaries and pregnant mares' serum gonadotrophin (PMSG) at pessary withdrawal. Luteal function was classified as inadequate when corpora lutea either failed to secrete progesterone completely, as assessed by twice daily peripheral blood samples, or caused a transient rise in progesterone lasting only 12-36 h. Lactation generally prolongs the duration of post-partum anoestrus (Mauleon & Dauzier, 1965;Kann & Martinet, 1975;Shevah et al, 1975;Kann et al, 1977) and is associated with reduced fertility at an induced oestrus during breeding and non-breeding seasons (Restall et al, 1978; (Hunter el al, 1955), held at 37°C in ovum culture medium (Flow Laboratories, Irvine, UK) (Wenham & Robinson, 1972).…”
mentioning
confidence: 99%